2019
DOI: 10.3390/ijms20143381
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Facilitates Skin Wound Healing by Increasing Angiogenesis and Inflammatory Cell Recruitment with Less Scar Formation

Abstract: Wound healing starts with the recruitment of inflammatory cells that secrete wound-related factors. This step is followed by fibroblast activation and tissue construction. Sphingosine-1-phosphate (S1P) is a lipid mediator that promotes angiogenesis, cell proliferation, and attracts immune cells. We investigated the roles of S1P in skin wound healing by altering the expression of its biogenic enzyme, sphingosine kinase-1 (SphK1). The murine excisional wound splinting model was used. Sphingosine kinase-1 (SphK1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…At this time, we do not yet know the biological consequences of this regulation in more complex setting, but there is reason to believe that they could be numerous. In fibroblasts, S1P signaling has been shown to increase wound healing in mice 45 , 46 . We speculate that the elevated O-GlcNAc levels in diabetes may attenuate S1P signaling with detrimental consequences for fibroblast biology in wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…At this time, we do not yet know the biological consequences of this regulation in more complex setting, but there is reason to believe that they could be numerous. In fibroblasts, S1P signaling has been shown to increase wound healing in mice 45 , 46 . We speculate that the elevated O-GlcNAc levels in diabetes may attenuate S1P signaling with detrimental consequences for fibroblast biology in wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have repeatedly demonstrated that S1P plays a critical role in angiogenesis [ 10 , 11 , 12 , 17 , 19 , 20 , 40 , 41 , 42 ]. In agreement with our mechanistic model [ 12 ], elevation of SphK1 , suppression of sphingosine kinase 2 ( SphK2 ), elevation of SPNS2 and Sphingosine-1-phosphate kinase receptor-1 ( S1PR1 ), all of which work to export S1P and promote angiogenesis, were associated with high score tumors (all p < 0.001, Figure 1 E).…”
Section: Resultsmentioning
confidence: 99%
“…Our group recently showed that topically applied sCA effectively transfects the wound bed in mice. 40 Wu et al. 18 also reported that if relatively large particles that contaminate sCA can be removed, the resulting purified sCA preparation is very safe in mice and monkeys.…”
Section: Discussionmentioning
confidence: 99%